Una sesión innovadora de trabajo de laboratorio para enseñar proceso de datos. Segundo curso de estudios de física a nivel universitario - Fondère, F.; Séré, M.G. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 1997)
An innovative reflection about measurement is proposed through Franck and Hertz experiment for second year University students. We present a sequence of laboratory work during which the students have the opportunity of deepening notions like dispersion, error and uncertainty, accuracy and precision, and some concepts of statistics. We describe how students are led to develop personal comments on their own results.